INVESTIGATING EMPLOYABILITY SKILL GAPS AMONG ENGLISH MAJOR STUDENTS IN ALGERIA - Mehdaoui, Ahmed (LLT Journal: A Journal on Language and Language Teaching, 2022)
As English plays an increasingly important role in today's job market, several studies have shown a direct correlation between English and employability. In Algeria, many Algerians believe that good English skills can help them get better jobs. However, in today's 21st century, as studies have proven, college graduates are more employable if they have skills that meet the demands of the modern workplace. The question that arises from this study is whether Algerian students majoring in English have the skills that will enable them to pursue successful careers. As far as we know, few studies address skill gaps among Algerian major students. Therefore, this study aims to examine the discrepancies between the skills that Algerian English major students are taught in comparison to the set of skills required for employment. To address this, this work applied a quantitative approach using a questionnaire administered to 40 undergraduate students from the Department of English at Ibn Khalodun University in Tiaret, Algeria. Key findings of this research revealed a gap in teamwork and research analysis skills, which are top-notch competencies for employers.